Basal cell carcinomas following roentgen therapy for lumbosacral rheumatic diseases - Baldari, U... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
During a 14-year survey 805 patients with basal cell carcinomas (BCCs) have been observed. 78 (9.7%) patients who presented tumors in the lumbosacral (LS)area had undergone local antiphlogistic x-ray treatment years before. Out of them 67 were men and 11 were women. All our patients received from 2 to 3 series, each of standardized 10 Gy. BCCs occurred earlier in the males than inthe females, as they had undergone the x-ray therapy at an earlier age. Fertile women did not undergo treatment in the LS area, because of vicinity ofthe gonads. The latency period from treatment to the tumor onset was quite long (average 19.2 years). According to the sun reactivity 7 persons (9%) belonged to the skin type I, 49 to type II (62.8%) and 22 (28.2%) to type III.There were no patients of types IV-VI. 70 patients (89%) had multiple lesions. Superficial pagetoid and pigmented tumors were diagnosed in 72 (92.3%) and fibroepithelial tumors (Pinkus) in 9 cases (11.5%). Our report points out that basal cell carcinomas following the x-ray therapy for lumbosacral rheumatic diseases were not uncommon in a dermatologist's practice.
Keywords: Adverse effects; Aged; Carcinoma, basal cell; Diagnosis; Etiology; Lumbosacral region; Middle age; Radiation effects; Retrospective studies; X-ray therapy